Literature on Tawhidi String Relation (TSR) Concept: A Text Mining - As-Salafiyah, Aisyah (Maqasid al-Shariah Review, 2023)
The universal paradigm presents concepts and applications, institutions, and a sustainable future or oneness of divine rule, which is referred to as monotheism. Economics, Finance, Society and Science are sub-systems of the supplemental global order system of Tawhidi String Relation (TSR). This study seeks to figure out the map of the development and trend of TSR published by well-known publications in the field of Economics and Finance. The data analysed were 50 research publications indexed by Google Scholar. The export data is then processed and analysed using the R Biblioshiny application program to determine the bibliometric map of TSR development. The conceptual structure of R 'biblioshiny' displays the network and the main research themes in a thematic map in the development of TSR theme research. The resulting mapping is in the form of most relevant words, word cloud, word treemap, word dynamic, trend topic, co-occurrence network, thematic map and thematic evolution. This study also provides a review of the literature related to the theme of TSR to be developed in future research. This study is the first comprehensive study that discusses the mapping development of trends in the TSR literature published in various scientific journals.